Intradural Schwannoma Exacerbating the Symptoms of Degenerative Lumbar Stenosis: Case Report - Lucas Crociati Meguins; Raphael dos Santos Abílio; Herbert Cunha Moreira Santos; Linoel Curado Valsechi; Elísio Eduardo Cardoso Duarte; Dionei Freitas de Morais (Brazilian Neurosurgery, 2017)
Abstract